The effect of ankle taping on vertical jump performance among amateur football players / Arif Muhaimin Zulkifli - Zulkifli, Arif Muhaimin (Faculty of Sports Science and Recreation, 2018)
The purpose of this study is to investigate the effect of ankle taping on vertical jump performance among amateur football players. A total of eighteen subjects (N=18) from Subang City Football Club were selected through purposive sampling. The study compared the differences between vertical jump performance with and without ankle taping. Sample Paired T-Test was used as this study included pre- and post-test using the group of subjects. During pre-test, all subjects performed three vertical jump tests without any application of ankle taping. After a minimum intervention of 24 hours, they performed the same test with the application of ankle tapings. Based on the Sample Paired T-Test result, there was no significant difference between vertical jump performances without ankle taping and vertical jump performance with ankle taping (p = 0.081). The overall result also indicated that vertical jump without taping (M = 40.33, SD = 5.77578) was inferior to vertical jump with taping (M = 41.31, SD = 5.78165). To conclude, this finding suggests ankle taping does not affect vertical jump performances among amateur football players and it does give positive mental effects for them to perform better.